2022
DOI: 10.1002/asia.202200669
|View full text |Cite
|
Sign up to set email alerts
|

A Novel EDOT/F Co‐doped PMIA Nanofiber Membrane as Separator for High‐Performance Lithium‐Sulfur Battery

Abstract: In this study, a novel fluorine-containing emulsion and 3, 4-ethylene dioxyethiophene (EDOT) co-doped poly-mphenyleneisophthalamide (PMIA) nanofiber membrane (EDOT/F-PMIA), as the separator of lithium-sulfur battery, was tactfully prepared via electrospinning. The multi-scale EDOT/ F-PMIA nanofiber membrane can be served as the matrix to fabricate gel polymer electrolyte (GPE). Furthermore, under the influence of fluorine-containing emulsion and EDOT, the PMIA-based GPE possessed excellent thermostability, emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Researchers coated flame-retardant materials on separators to enhance the safety of the separator. 128 On one hand, these coatings can block heat from reaching the separator, preventing thermal shrinkage. 129 On the other hand, the flame-retardant groups in the coating can form a protective layer and dilute flammable gases, achieving synergistic flame retardancy in both the gas and condensed phases.…”
Section: Multifunctional Flame-retardant Separators and Interlayersmentioning
confidence: 99%
“…Researchers coated flame-retardant materials on separators to enhance the safety of the separator. 128 On one hand, these coatings can block heat from reaching the separator, preventing thermal shrinkage. 129 On the other hand, the flame-retardant groups in the coating can form a protective layer and dilute flammable gases, achieving synergistic flame retardancy in both the gas and condensed phases.…”
Section: Multifunctional Flame-retardant Separators and Interlayersmentioning
confidence: 99%
“…One method is to modify PMIA NFs with a fluorinated emulsion. Xiang et al [ 78 ] found that fluorination decreased the electrolyte contact angle from 66⁰ to 23⁰ and increased electrolyte uptake by 12%. The highly polar fluorine groups also reduced pore size by 18% but increased pore volume by 60%, resulting in improved LiPS rejection while maintaining high Li-ion diffusion.…”
Section: Novel Nanofiber Separatorsmentioning
confidence: 99%
“…Modification of the separator is a simple and effective method to inhibit the "shuttle effect". Therefore, more and more researchers have paid much more attention to modifying the separator in Li-S batteries to inhibit lithium polysulfide shuttling to the negative electrode [15] . HY Xiang et al prepared a nanofiber membrane 3, 4-ethylene dioxyethiophene/ F co-doped poly-m-phenyleneisophthalamide (EDOT-5/F-PMIA) by electrospinning technology [16] .…”
Section: Introductionmentioning
confidence: 99%